The Role of Low-dose of Aspirin in Improving the Subsequent Live-Birth Rate Amongst Women with Unexplained Recurrent Miscarriage - نعيسه, ثورة (Latakia University Journal -Medical Sciences Series, 2020)
The aim of the study: to assess the value of low-dose aspirin (81mg) daily in Improving the subsequent live-birth rate amongst women with unexplained recurrent miscarriage. In the case of early miscarriage < 13 gestational weeks, there are two groups: Group I: Took aspirin, The live-birth rate was (46.6%) Group II: Didn’t take aspirin, the live-birth rate was (43.3%) There was no significant differences in live-birth rate between those who took aspirin and those who didn’t take it, in women with previous early miscarriage. In contrast, women with previous late miscarriage who took aspirin had a significantly high live birth rate compared with those who didn’t take aspirin.